2011
DOI: 10.3233/nre-2011-0635
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative treatment with Botulinum Toxin A before total hip arthroplasty in a patient with tetraspasticity: Case report and review of literature

Abstract: We report on a patient with tetraspasticity due to perinatal cerebral palsy requiring total hip joint endoprosthesis because of hip dysplasia. In order to minimize the risk of postoperative luxation Botulinum Toxin A was injected preoperatively into hip flexor and adductor muscles guided by CT-fluoroscopy. Outcome measures included muscle tone, limb position and self-reported pain relief. Seven days post injections the tone of the right hip flexor and adductor muscles improved from three to one points on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The adverse effects reported with the use of BoNT‐A include muscle weakness and atrophy at the injection site, muscle pain, headache, fever, arterial hypertension, diarrhoea and abdominal pain (Finiels and Batifol 2010). However, no systemic or local adverse effects were noted in the present study from either treatment, which is consistent with previous studies (Layeeque and others 2004, Singh and others 2010, Eibach and others 2011).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The adverse effects reported with the use of BoNT‐A include muscle weakness and atrophy at the injection site, muscle pain, headache, fever, arterial hypertension, diarrhoea and abdominal pain (Finiels and Batifol 2010). However, no systemic or local adverse effects were noted in the present study from either treatment, which is consistent with previous studies (Layeeque and others 2004, Singh and others 2010, Eibach and others 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The classical mechanism of action of BoNT‐A involves the inhibition of acetylcholine release from cholinergic nerve endings, which produces potent muscle relaxation (Aoki 2005). However, several reports suggest that this toxin has an antinociceptive effect that is independent of its neuromuscular activity (Bach‐Rojecky and Lacković 2005, Singh and others 2010, Eibach and others 2011). In vitro studies demonstrated that BoNTs inhibit the release of various neurotransmitters, including glutamate, gamma aminobutiryc acid, aspartate and catecholamine from cerebral synaptosomes, chromaffin cells, central neurons and hippocampal slice cultures (Ashton and Dolly 1988, Capogna and others 1997 ; Keller and others 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with hip OA, pain may be a consequence of prolonged or excessive contraction of the adductor muscles and Botulinum NeuroToxin serotype A (BoNT-A) could be proposed as an effective treatment [ 15 ]. It is known that BoNT-A is used for treatment of spasticity of the hip adductors and injections of BoNT-A have been used as an adjunctive measure to prevent or delay lateral migration of the femoral head in children with cerebral palsy [ 16 , 17 ]. It is hypothesized that BoNT-A injection into selected muscles involved in hip movements will reduce the pressure transferred by the femoral head against the acetabulum, as is achieved with the Voss operation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%